Every True Pleasure : LGBTQ Tales of North Carolina - Barnhardt, Wilton (Book collections on Project MUSE., 2019)
"North Carolina's finest fiction and non-fiction writers come together in Every true pleasure, including David Sedaris, Kelly Link, Allan Gurganus, Randall Kenan, and more. Within the volume--featuring writers who identify as gay, trans, bisexual, and straight--are stories and essays that show the full spectrum of contemporary life though an LGBTQ lens. These writers, some native to the state, others born elsewhere, but all with ties to North Carolina, show the multifaceted challenges and joys of LBGTQ life: religion and how it's wielded, young love and gay panic, surrogate pregnancies, military service, family life, finding sex and one's true gender, and discovering love"--